2019
DOI: 10.1021/acsaem.9b00079
|View full text |Cite
|
Sign up to set email alerts
|

Oriented p–n Heterojunction Ag2O/Zn(O,S) Nanodiodes on Mesoporous SiO2 for Photocatalytic Hydrogen Production

Abstract: Hydrogen is a great candidate fuel to replace fossil fuels in the future since it has high energy density, zero-emission, and renewability. Here, we report our design with p-type Ag2O and n-type Zn­(O,S) loaded on mesoporous silica to form SiO2/Ag2O/Zn­(O,S) with the nano p–n heterojunction to improve the efficiency of photocatalytic hydrogen evolution reaction (HER). The photocatalysts were systematically characterized to identify their properties. Through the optimization of the Zn­(O,S)-loaded amount and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…The Mo 4+ , Mo 6+ , and Mo defect ratios are 35.7, 49.4, and 14.9%, respectively. Figure c reveals the existence of Ag + in NAM-1 with Ag 3d 5/2 and 3d 3/2 orbitals at 363.9 and 369.9 eV, respectively, which are consistent with previous works. ,, Figure d indicates that the orbitals of Ni 2+ 2p 3/2 and 2p 1/2 are located at 856.4 and 874.3 eV, respectively, with a spin-energy separation of ∼17.7 eV and two satellite peaks. The oxygen analysis with high-resolution XPS shows three states of oxygen in chemisorbed water, hydroxides, and oxides bonded to nickel. The oxygen 1s orbitals after deconvolution revealed oxide, hydroxide, and chemisorbed oxygen, which were noticed at 529, 531, and 532.2 eV, respectively, as indicated in Figure e, agreed well with the previous work on Ni­(OH) 2 .…”
Section: Results and Discussionsupporting
confidence: 88%
“…The Mo 4+ , Mo 6+ , and Mo defect ratios are 35.7, 49.4, and 14.9%, respectively. Figure c reveals the existence of Ag + in NAM-1 with Ag 3d 5/2 and 3d 3/2 orbitals at 363.9 and 369.9 eV, respectively, which are consistent with previous works. ,, Figure d indicates that the orbitals of Ni 2+ 2p 3/2 and 2p 1/2 are located at 856.4 and 874.3 eV, respectively, with a spin-energy separation of ∼17.7 eV and two satellite peaks. The oxygen analysis with high-resolution XPS shows three states of oxygen in chemisorbed water, hydroxides, and oxides bonded to nickel. The oxygen 1s orbitals after deconvolution revealed oxide, hydroxide, and chemisorbed oxygen, which were noticed at 529, 531, and 532.2 eV, respectively, as indicated in Figure e, agreed well with the previous work on Ni­(OH) 2 .…”
Section: Results and Discussionsupporting
confidence: 88%
“…It has been proposed that the combined effects of enhanced light harvesting, enlarged specific surface area (129 m 2 /g), hindered recombination of charge carriers, negatively shifted CB position, and an efficient exposure of active sites, are responsible for high photocatalytic activity (Figure 18). Another specific 3D structure has been presented by Gultom et al; a nanodiode of Ag2O and Zn(O,S), deposited on the surface of mesoporous silica to form the p-n heterojunction SiO2/Ag2O/Zn(O,S), as illustrated in Figure 19 [147]. It was found that the photocatalytic hydrogen generation has been obviously enhanced for the composite of n-Zn(O,S) with p-Ag2O (outward for improvement of reduction reactions, and inward for modulating the built-in electrical nanofield).…”
Section: Three-dimension (3d) Photocatalystsmentioning
confidence: 99%
“…The remarkable enhancement of activity has been ascribed to the synergy between components via the following: (i) three-dimensional multi-bandgap quantum-well (3D MQW) band structure, (ii) improved photoabsorption, (iii) activity of surface oxygen, (iv) separation of charge carriers, (v) longer lifetime of charges, (vi) low charge transfer resistance, and (vii) the p-n heterojunction in the photocatalyst. Another specific 3D structure has been presented by Gultom et al; a nanodiode of Ag2O and Zn(O,S), deposited on the surface of mesoporous silica to form the p-n heterojunction SiO2/Ag2O/Zn(O,S), as illustrated in Figure 19 [147]. It was found that the photocatalytic hydrogen generation has been obviously enhanced for the composite of n-Zn(O,S) with p-Ag2O (outward for improvement of reduction reactions, and inward for modulating the built-in electrical nanofield).…”
Section: Three-dimension (3d) Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the preparation of heterojunction photocatalysts, it is of great signicance to design a heterojunction photocatalyst which can adjust the heterojunction two-phase energy band structure. On the basis of research by the same research group, 55,56 MoCoOS, a Z-scheme heterojunction catalyst prepared by simple hydrolysis of molybdenum and cobalt, has better hydrogen production capacity and excellent pollutant reduction capacity compared with other catalysts.…”
Section: Introductionmentioning
confidence: 99%